Do Security Analysts Discipline Credit Rating Agencies?. Issue 4 (19th May 2022) - Fong, Kingsley; Hong, Harrison; Kacperczyk, Marcin; Kubik, Jeffrey D
Abstract: Credit ratings of corporations are biased, but the forces driving this bias are unclear. We argue it would be difficult for rating agencies to issue high grades for a firm's debt when there are a lot of objective equity analyst reports about the firm's earnings that are informative about its default. We find that an exogenous drop in analyst coverage leads to greater optimism-bias in ratings, especially for firms with little bond analyst coverage and those that are close to default. This coverage-induced shock leads to less informative ratings about future defaults and downgrades and more subsequent bond security mispricings. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.